The gating pore blocker 1-(2, 4-xylyl)guanidinium selectively inhibits pacemaking of midbrain dopaminergic neurons. (1st October 2021) - Jehasse, Kevin; Massotte, Laurent; Hartmann, Sebastian; Vitello, Romain; Ringlet, Sofian; Vitello, Marie; Chua, Han Chow; Pless, Stephan A.; Engel, Dominique; Liégeois, Jean-François; Lakaye, Bernard; Roeper, Jochen; et al.
Abstract: Although several ionic mechanisms are known to control rate and regularity of the slow pacemaker in dopamine (DA) neurons, the core mechanism of pacing is controversial. Here we tested the hypothesis that pacemaking of SNc DA neurons is enabled by an unconventional conductance. We found that 1-(2, 4-xylyl)guanidinium (XG), an established blocker of gating pore currents, selectively inhibits pacemaking of DA neurons. The compound inhibited all slow pacemaking DA neurons that were tested, both in the substantia nigra pars compacta, and in the ventral tegmental area. Interestingly, bursting behavior was not affected by XG. Furthermore, the drug did not affect fast pacemaking of GABAergic neurons from substantia nigra pars reticulata neurons or slow pacemaking of noradrenergic neurons. In DA neurons, current-clamp analysis revealed that XG did not appear to affect ion channels involved in the action potential. Its inhibitory effect persisted during blockade of all ion channels previously suggested to contribute to pacemaking. RNA sequencing and voltage-clamp recordings yielded no evidence for a gating pore current to underlie the conductance. However, we could isolate a small subthreshold XG-sensitive current, which was carried by both Na + and Cl − ions. Although the molecular target of XG remains to be defined, these observations represent a step towards understanding pacemaking in DA neurons. Highlights: XG seems to be the first specific inhibitor of pacemaking in midbrain DA neurons. No evidence for gating pore currents was found in DA neurons. XG blocks a small subthreshold current carried by both Na + and Cl − XG did not interact with DAT. The target of XG remains to be found.